SOCIALIZATION OF ADMINISTRATIVE SERVICES IN THE RESEARCH AND COMMUNITY SERVICE INSTITUTION AT NIAS RAYA UNIVERSITY - Harefa, Darmawan; Laia, Bestari; Laia, Firdaus; Tafonao, Aluiwaauri (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service is to provide understanding to the students in facilitating the services at the Research and Community Service Institution of Nias Raya University. Accessible services can save time, ensuring students do not have to wait too long for various matters at the Research and Community Service Institution of Nias Raya University. The methods used in this service are lectures and direct socialization delivered to students dealing with the Research and Community Service Institution of Nias Raya University. The results from this service show progress in the previously time-consuming administrative processes, with fast and efficient service experienced by the students. In conclusion, the administrative services at the Research and Community Service Institution of Nias Raya University are currently well-coordinated, and the impact can be felt by all students who have experienced the services provided. A suggestion for this service activity is to conduct regular evaluations of the services provided by the Research and Community Service Institution of Nias Raya University, both from the institution's team and the students who feel they have not received optimal service.